What's real, what's ideal : overcoming a negative body image - Davis, Brangien (New York : Rosen Pub. Group, 1999)
Examines the causes and consequences of negative feelings about one's body and discusses ways to develop a more positive and accepting self-awareness.
Includes bibliographical references (p. 62) and index.
Keywords: Body image in adolescence -- Juvenile literature; Eating disorders in adolescence -- Juvenile literature; Self-perception -- Juvenile literature